A Model of Character Education of Peace Love in Muhammadiyah Vocational School Post of COVID-19 Pandemic - Parjiman Parjiman; Sutarman Tarman Wiryareja (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
The purpose of this study is to delve into the depths associated with: (1) Muhammadiyah's values-based peace-loving character education model in SMK Muhammadiyah 1 Bangunjiwo Kasihan Bantul after the COVID-19 pandemic; (2) Factors supporting Muhammadiyah values-based peace-loving character education in SMK Muhammadiyah 1 Bangunjiwo Kasihan, Bantul after the COVID-19 pandemic. (3) the benefits of peace-loving character education in changing the students' character values, and behavior of SMK Muhammadiyah 1 Bagunjiwo Kasihan Bantul Yogyakarta students. The research methodology of this study is a qualitative research methodology with a descriptive approach.The result of this research shows that a peace-loving character education model was found based on Muhammadiyah values at SMK Muhammadiyah 1 Bangunjiwo Kasihan Bantul during the post-COVID-19 pandemic, including: (1) Duha prayers are held show every morning; (2) Before the joint learning of reading al-Qur'an; (3) da'wah; (4) performing midday and afternoon prayers in the congregation; (5) Every Friday it is obligatory to carry out Friday prayers in school; (6) There are Hizbul Waton activities; (8) Morning Apple Ceremony; (9) There is moral education in schools. The impact of peace-loving character education on the transformation of character values and behavior of students at SMK Muhammadiyah 1 Bagunjiwo Kasihan Bantul Yogyakarta are transformations of changes in daily behavior for the better, such as students care more about their fellow friends, teachers, school leaders and towards the people in the surrounding community.